2019
DOI: 10.1017/s0950268818003539
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological evaluation of human papillomavirus genotypes and their associations in multiple infections

Abstract: The aim of this study was to determine the frequency of multiple type human papillomavirus (HPV) infections, and whether any types are involved in multiple HPV-type infections (mHPV) more or less frequently than expected. From January 2012 to February 2018, 2848 cervico-vaginal swabs were analysed in the UOC Microbiology and Virology of Policlinico of Bari, Italy. HPV DNA detection was performed using initially nested-polymerase chain reaction (PCR) and subsequently multiplex real-time PCR assay. 1357/2848 sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 38 publications
1
19
0
3
Order By: Relevance
“…These data indicate that development of HSIL is associated with an increase in the viral load of high-risk HPVs but could also be associated with a concomitant decrease in the viral load of some low-risk types. In this regard, low-risk HPV42 was found to be the most common HPV type detected in cervical smears collected from women in the Apulia region of Italy although it is acknowledged that there are significant variations in HPV types present with respect to different geographical locations [ 14 ].…”
Section: Hpv Types and Associated Pathologiesmentioning
confidence: 99%
“…These data indicate that development of HSIL is associated with an increase in the viral load of high-risk HPVs but could also be associated with a concomitant decrease in the viral load of some low-risk types. In this regard, low-risk HPV42 was found to be the most common HPV type detected in cervical smears collected from women in the Apulia region of Italy although it is acknowledged that there are significant variations in HPV types present with respect to different geographical locations [ 14 ].…”
Section: Hpv Types and Associated Pathologiesmentioning
confidence: 99%
“…Persistent infection by viral types of high oncogenic risk, mainly by HPV types 16 and 18, is one of the main factors for the development of cervical cancer. Many co-factors contribute to the persistent HPV infection and the progression of cervical lesions, including biological, behavioral, and environmental factors, as well as other sexually transmitted infections (STIs) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in the last decade, a large number of studies have shown coinfections with different HPV types. Some of these studies used high throughput sequencing (HTS) [ 13 ], revealing that infections with multiple HPV types are common and are associated with an increased risk of carcinogenesis [ 14 , 15 ], mainly in cervical cancer [ 14 , 16 18 ]. The combination of HPV types, and the presence of high-risk (HR) HPV (i.e.…”
Section: Introductionmentioning
confidence: 99%